Design and Implementation of Programmable Sequence Controller Based on FPGA - Juguang Li; Fan Wang; Hua Zhang (2013 International Conference on Computer Sciences and Applications, 2013)
This paper, based on Altera Cyclone II FPGA, introduces a programmable sequence controller design scheme with a feature of multichannel (16 in this paper) and high-precision waveform output. The controller's output mode (single pulse and PWM pulse) and various parameters such as delay and duty cycle etc of each output pulse are independently adjustable, and high-precision output pulse could be adjusted according to actual demand. The system uses AT91SAM9260 processor as the main controller and monochromatic LCD as interactive media, and configures required parameters through local keyboard (or remote control). Results show that the system is not only easy to understand and simple in the entire operating process, but also has very important practical significance.